Test of the Randomness of Residuals and Detection of Potential Outliers for the Modified Logistics Used in the Fitting of the Growth Curve of Immobilized Pseudomonas putida on Phenol (Journal of Environmental Microbiology and Toxicology, 2022)
As a result of the fact that several research do not carry out statistical diagnostics on the nonlinear model that was employed, the data could not be random. Because these systems rely on random data, this is a necessity for all parametric statistical assessment procedures. The Wald–Wolfowitz runs test was done on the modified logistics that were employed in the fitting of the growth curve of immobilized Pseudomonas putida on phenol. This test was carried out in order to determine whether or not the logistical changes had any effect on the growth curve. This test was carried out so that it could be determined whether or not the adjustments made to the logistical processes were successful. The runs test showed that there was a total of eight runs, which contradicts the expectation that there would only be seven runs due to the unpredictability of the circumstance. The assumption was based on the fact that there would only be seven runs. Since the p-value was larger than 0.05, the null hypothesis is not rejected; this suggests that there is no convincing evidence of the non-randomness of the residuals; rather, the residuals represent noise in the data. As a consequence of the findings of Grubb's test, which indicate that there is no outlier, it is not necessary to reanalyze the data because the modified logistics model used in the fitting of the growth curve of immobilized Pseudomonas putida on phenol was adequate enough. This means that the reanalysis would be unnecessary.
Keywords: Wald–Wolfowitz runs test; Modified logistics; Pseudomonas putida; Phenol; Grubb’s test